Atlantoaxial Rotatory Fixed Dislocation: Report on a Series of 32 Pediatric Cases. Issue 12 (June 2016) - Wang, Shenglin; Yan, Ming; Passias, Peter G.; Wang, Chao
Abstract : Study Design: Retrospective case series of atlantoaxial rotatory fixed dislocation (AARFD). Objective: To describe clinical features and the surgical treatment of AARFD. Summary of Background Data: The classification and treatment strategy for atlantoaxial rotatory fixation (AARF) were previously described and remained controversial. AARF concomitant with atlantoaxial dislocation has different clinical features and treatment strategy with the most AARF. Due to deficiency of the transverse ligament or odontoid, the atlantoaxial remains unstable even after the torticollis relieved or cured. Because of the rarity, treatment strategy for this special condition has not been specialized and fully explored in the literatures. Methods: Thirty-two children with AARFD (sustained torticollis more than 6 weeks and atlanto-dental internal more than 5 mm) were retrospectively reviewed. Treatment methodology, pearls, and pitfalls of the treatment were discussed. Results: Thirty-two cases had sustained torticollis for an average of 5.7 months. ADI of them ranged from 8 to 22 mm, with a mean of 11.3 mm. Eight cases presented with signs and symptoms of spinal cord dysfunction. All 32 cases underwent surgery and had no spinal cord or vertebral artery injury. The surgery included posterior reduction and fusion (reducible dislocation and torticollis, 16 cases), and transoral release followed by posterior reduction and fusion (irreducible dislocation and torticollis, 16 cases). The average follow-up time was 42 months. Solid fusion and torticollis healing were achieved in 31 patients (96.9%) as detected radiologically. Two cases (6.3%, 2/32) suffered complications (cerebrospinal fluid leakage and recurred torticollis followed by revision). Conclusion: AARFD had distinct clinical features relative to common presentations of AARF. Because of deficiency of the transverse ligament or odontoid and subsequent atlantoaxial dislocation, surgical treatments are applied for this condition, including transoral release and posterior C1–2 reduction and fusion. AARFD cases were successfully managed surgically without preoperative traction, with few complications seen. Level of Evidence: 4